An intrusion tolerant system for improving availability in smart grid control centers. - Tanha, Maryam; Hashim, Fazirulhisyam (2012)
In this paper, we propose an intrusion tolerant security system for crucial components in the SCADA systems and control centers of smart grid. Due to the widespread and dramatic social and economic effects of the failure, power outage or malfunction of the smart grid, likely cyber security threats need to be dealt with vigilantly. The level of security required for ICT which is an integral part of the smart grid does not suffice for the critical operation of the smart grid. Thus, intrusion tolerant approach plays an important role for hardening smart grid to achieve the goal of survivability and continuity of service in the presence of malicious attacks and can be considered as a complementary solution to the conventional security mechanisms. Availability analysis of the proposed intrusion tolerant system demonstrates enhanced availability in comparison with the other two known existing intrusion tolerant architectures.